ANALYSIS OF THE WORLD HELICOPTER MARKET AND PERSPECTIVE OF HIS DEVELOPMENT - Казак, В.; Огир, А. (Science-based technologies, 2011)
An important feature of the modern helicopter is a stable market demand both in military and civilian helicopters. In a helicopter of an important part of research is prediction of the world helicopter market to create competitive and efficient and cost effective construction helicopters in aviation industry.